Natural history of silent lacunar infarction: 10-year follow-up of a community-based prospective study of 0.5 million Chinese adults - Zilong Hao; Yiping Chen; Neil Wright; Haiqiang Qin; Iain Turnbull; Yu Guo; Christiana Kartsonaki; Sam Sansome; PeiPei; Canqing Yu; Qijun Gu; Jianming Hu; et al. (Elsevier, 2021)
Background: Widespread use of brain imaging in China has resulted in an increased prevalence of silent lacunar infarct (LACI) in addition to symptomatic LACI, but their clinical relevance is not fully understood. Methods: We compared the 5-year risks of recurrent stroke and all-cause mortality for silent LACI vs symptomatic LACI in a prospective study of 489,597 Chinese adults with no history of stroke or ischemic heart disease at baseline. Data on recurrent stroke and all-cause mortality were obtained by linkage with local stroke and mortality registries and health insurance records for all hospital admissions. Findings: Among 12,150 cases with an adjudicated diagnosis of first-ever LACI, 4,134 (34%) had silent LACI and 8,016 (66%) had symptomatic LACI. All cases had brain imaging, but only 33% of silent LACI and 40% of symptomatic LACI cases had brain magnetic resonance imaging (MRI). The standardized event rates for silent LACI were 2-fold greater in urban than rural areas, but the ratios of silent LACI vs symptomatic LACI were similar in all areas. Cases with silent LACI vs symptomatic LACI had comparable 5-year risks of recurrent stroke (38% vs 43%) and all-cause mortality (11% vs 14%), respectively. For both silent and symptomatic LACI cases, most cases of recurrent stroke had non-LACI (70% vs 72%). While the relative risks of recurrent stroke did not differ by age, sex and area, the absolute risks of all-cause mortality varied by sex, age and area. Interpretation: The prognosis of cases with silent LACI was comparable with symptomatic LACI, and the results highlight the need for further randomized trials assessing the efficacy and safety of established treatments for ischemic stroke in cases with silent LACI. Funding: Wellcome Trust (212946/Z/18/Z, 202922/Z/16/Z, 104085/Z/14/Z, 088158/Z/09/Z) and National Key Research and Development Program of China (2016YFC0900500, 2016YFC0900501, 2016YFC0900504, 2016YFC1303904) and National Natural Science Foundation of China (91843302); UK Medical Research Council (MC_UU_00017/1,MC_UU_12026/2 MC_U137686851), Cancer Research UK (C16077/A29186; C500/A16896) and British Heart Foundation (CH/1996001/9454). ZH was supported West China Hospital, Sichuan University (ZYGD18009 and 2016YFC1300505) for a visiting scholarship to the University of Oxford, UK, during 2018-19.